Early Upper Paleolithic chronology in the Levant: new ABOx-SC accelerator mass spectrometry results from the Mughr el-Hamamah Site, Jordan. Issue 85 (August 2015) - Stutz, Aaron Jonas; Shea, John J.; Rech, Jason A.; Pigati, Jeffrey S.; Wilson, Jim; Belmaker, Miriam; Albert, Rosa Maria; Arpin, Trina; Cabanes, Dan; Clark, Jamie L.; Hartman, Gideon; Hourani, Fuad; et al.
Abstract: Methodological developments and new paleoanthropological data remain jointly central to clarifying the timing and systemic interrelationships between the Middle-Upper Paleolithic (MP-UP) archaeological transition and the broadly contemporaneous anatomically modern human-archaic biological turnover. In the recently discovered cave site of Mughr el-Hamamah, Jordan, in situ flint artifacts comprise a diagnostic early Upper Paleolithic (EUP) assemblage. Unusually well-preserved charcoal from hearths and other anthropogenic features associated with the lithic material were subjected to acid-base-wet oxidation-stepped combustion (ABOx-SC) pretreatment. This article presents the ABOx-SC accelerator mass spectrometry (AMS) radiocarbon dates on nine charcoal specimens from a single palimpsest occupation layer. Date calibration was carried out using the INTCAL13 radiocarbon calibration dataset. With the bulk of the material dating to 45–39 ka cal BP (thousands of years calibrated before present), the Mughr el-Hamamah lithic artifacts reveal important differences from penecontemporaneous sites in the region, documenting greater technological variability than previously known for this time frame in the Levant. The radiocarbon data from this EUP archaeological context highlight remaining challenges for increasing chronological precision in documenting the MP–UP transition.